Investment, Hysteresis, and Layers of Techniques: A Case Study of Agricultural Manufacturing Machinery in Multan Division (The Pakistan Development Review, 1999)
The behaviour of firms is still a little understood matter. Why one firm or industry is investing more than the other or what makes a firm enter or exit from the market, what are the psychological factors that go to make a choice of this kind are questions that have not been answered satisfactorily. Concepts like irreversibility, uncertainty, investment, and the value of waiting are very much there in the literature, e.g., McDonald and Siegel (1985, 1986); Nickell (1974); Schmalensee (1972); Hartman (1972); Henry (1974) and LAM (1989) and others. But the psychology of decision-making on the face of losses has not received much attention in the literature. That the Economic Hysteresis1 and Layers of Techniques2, developed by Professor A. Dixit and Professor P. N. Mathur respectively tackle. The former is discussed by Pindyck (1988, 1991, 1992) and Dixit (1989, 1989a, 1991, 1992); while Mathur (1977, 1989, 1990); Law and Azid (1993); Azid and Ghosh (1998) and Rashid (1989,1989a) have discussed the latter.